Taxonomic revision of the genus Neopleurophora Brown (Diptera: Phoridae), with the description of thirty seven new species - Ament, Danilo Cesar; Amorim, Dalton De Souza (Zootaxa, 2013)
Thirty seven new Neotropical species of the phorid genus Neopleurophora are described—N. acrensis, sp. nov., N. acrochaetopyga, sp. nov., N. atlantica, sp. nov., N. balbii, sp. nov., N. boliviana, sp. nov., N. brachypyga, sp. nov., N. brachytarsus, sp. nov., N. browni, sp. nov., N. carcharopyga, sp. nov., N. cauca, sp. nov., N. ceratopyga, sp. nov., N. chocoensis, sp. nov., N. colobopyga, sp. nov., N. costaricana, sp. nov., N. dichaeta, sp. nov., N. dicrodrilus, sp. nov., N. diffusa, sp. nov., N. dolichopyga, sp. nov., N. dorsimaculata, sp. nov., N. hymenodrilus, sp. nov., N. kleini, sp. nov., N. kungi, sp. nov., N. lamasi, sp. nov., N. manauara, sp. nov., N. marquesi, sp. nov., N. megalopyga, sp. nov., N. microssoma, sp. nov., N. odontopyga, sp. nov., N. platypyga, sp. nov., N. polychaetopoda, sp. nov., N. prionotopyga, sp. nov., N. ptychodrilus, sp. nov., N. reginensis, sp. nov., N. scleropyga, sp. nov., N. setiventris, sp. nov., N. synaptodrilus, sp. nov., N. tanytarsus, sp. nov. The female holotypes of N. scutellata and N. scutellata var. jamaicensis could not be associated to any male specimen and there is no sufficient morphological evidence to consider either as different species. Neopleurophora setipes is redescribed and illustrated. The hypopygial morphology is studied in detail and the first illustrations of the phallus of the genus are presented. An identification key for the species of the genus is provided and groups of species are proposed.